2019
DOI: 10.31557/apjcp.2019.20.10.3051
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological Characteristics and Mutational Analysis of Gastrointestinal Stromal Tumors from India: A Single Institution Experience

Abstract: Background: Gastrointestinal stromal tumor (GIST) is the most common type of mesenchymal neoplasm of gastrointestinal tract. The incidence of GIST in India is not known and its treatment strategy in our country is largely derived from studies in other global populations. Some of the most important features of this type of cancer include its size, site of origin, mitotic index, histology and Immunohistochemistry. In this report we have studied these parameters in the Indian GIST patients presenting at our cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…In a study by Minhas et al as well stomach was the most common site of the tumor. 7 In our study GIST was more common in males than females consistent with the studies conducted in other parts of the country. 7,8 Age of the patients varied from 25 years to 76 years with 50 years as median age of diagnosis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a study by Minhas et al as well stomach was the most common site of the tumor. 7 In our study GIST was more common in males than females consistent with the studies conducted in other parts of the country. 7,8 Age of the patients varied from 25 years to 76 years with 50 years as median age of diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…7 In our study GIST was more common in males than females consistent with the studies conducted in other parts of the country. 7,8 Age of the patients varied from 25 years to 76 years with 50 years as median age of diagnosis. The various sites of lesion in our study were stomach, ileum, jejunum, esophagus, rectum and in two patients the exact origin could not be ascertained.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the germline KIT p.(Met541Leu) variant was found in 9% of TETs. To date, Met541Leu has mostly been reported in GISTs, in which it is associated with an increased risk of tumour progression and dissemination [ 81 , 82 , 83 ]. Using transfected cell lines, Brahmi et al found that KIT p.(Met541Leu) induced mutant-like intracellular signalling in the presence of stem cell factor [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indian data describing and analysing the mutations is sparse [11][12][13][14]. Minhas et al [15] and Cyriac et al [16] described a cohort of 31 and 24 patients, respectively, wherein c-kit was the most common mutation seen. SDH deficiency, wild type and PDGFRA D842V molecular alterations have been incorporated in the guidelines to better understand the extensive clonal heterogeneity observed in patients with GIST.…”
Section: Introductionmentioning
confidence: 99%